Pengaruh Kualitas Pelayanan Pajak, Pelaksanaan Pemeriksaan Pajak, Dan Modernisasi Sistem Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Pribadi (Studi Pada Kpp Pratama Malang Selatan) - Fina idamatul Fitri; Muhammad Mansur; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTTaxpayer compliance is an act of obeying the law. There are issues with taxpayer compliance, such as tax evasion, which will lead to declining tax revenues. Behind all that there are factors that cause decreased taxpayer compliance, which is, taxpayer dissatisfaction with public services and administrative systems used too convoluted and consuming a lot of taxpayer time, Therefore, it needs to be done repair in terms of the server and administration system with the support of tax audit on taxpayers. In this research aims to determine the influence of the quality of tax service, the implementation of tax audit and the modernization of the tax administration system to the taxpayer compliance at KPP Pratama South Malang. The research is a quantitative study using primary data. Collection of data on this research using instrument questionnaire. The questionnaire distributed as much as 100 to the taxpayer as the respondent. The technique used is random sampling. Data analysis using multiple linear regression using SPSS Analysis program version 25 tool. Based on the results of the analysis in this study stated that simultaneously the quality of tax services, the implementation of tax checks, and the modernization of taxation administration system significantly affect the personal mandatory compliance. As for a partial good quality of tax service, implementation of tax checks, and modernization of the taxation administration system has a positive and significant influence on the compliance of personal taxpayers. Keywords: Tax Service quality, implementation of tax audit, modernization of taxation administration system, taxpayer compliance.